Identification of functional regions on the I-Ab molecule by site-directed mutagenesis. - Cohn, L E (1986)
Functional analysis of mutant class II major histocompatibility complex molecules has begun to identify regions important for antibody binding and for T-cell activation. By using in vitro mutagenesis directed at the beta 1 domain of the Ab beta gene we have constructed three structurally distinct mutant Ab beta genes. Each of these genes, as well as the wild-type Ab beta gene, was cotransfected together with the wild-type Ab alpha gene into the Ia-negative B-lymphoma cell line M12.C3. Transfection resulted in the successful synthesis and cell surface expression of three mutant class II antigens that showed serological and functional alterations as compared to the I-Ab antigens from the M12.C3 cell transfected with the wild-type gene. The variable patterns of both I-Ab-specific monoclonal antibody binding and activation of I-Ab-specific T-cell hybridomas show that the mutations result in the loss of structural epitopes required for both monoclonal antibody binding and for T-cell recognition. The data suggest that there are multiple sites on a single Ia molecule that are recognized by T helper cells and also that the tertiary conformation of the Ia molecule can be critical in the formation of such sites.